COMPARATIVE PERFORMANCE STUDY OF DIFFERENT OAT VARIETIES UNDER AGRO-CLIMATIC CONDITIONS OF SIBI - M. Y. Lodhi; I. B. Marghazani; K. Hamayun; M. J. Marri (Journal of Animal and Plant Sciences, 2009)
Fodders are the main source of animal feed in Sibi region. However, the yield per acre is still far below than optimum level of production. Considering such a miserable picture in the region, a series of different fodder production trials were initiated at Large Ruminant Research Institute, Sibi. In the present study, nine cultivars of oats (Avena sativa) were evaluated for different yield components during November, 2007 to January, 2008. Data on plant height, leaf area and fodder yield per unit area were recorded. Differences among cultivars were considered as significant (P< 0.05). The results further revealed that variety No. 725 excelled over all other varieties in higher fresh fodder yield (47.6 kg/hectare) under agro-climatic conditions of Sibi. However, further studies are needed in order to recommend a suitable variety for general cultivation to meet increasing demand of fodder in the region.
Keywords: Oats; improved varieties; agro-climatic conditions; Sibi; Pakistan